(untitled) (Zaporizhzhia Historical Review, 2021)
The goal of this the article is to demonstrate the influence of the Ukrainian Cossack world outlook over the black letter book early in the XVII century. The sources used in the investigation are kept in one of the oldest libraries in Ukraineís ñ in M. Gorky State Scientific Library of Odessa.